Fast Na‐Ion Intercalation in Zinc Vanadate for High‐Performance Na‐Ion Hybrid Capacitor. Issue 35 (23rd October 2018) - Huang, Haijian; Kundu, Dipan; Yan, Runyu; Tervoort, Elena; Chen, Xi; Pan, Long; Oschatz, Martin; Antonietti, Markus; Niederberger, Markus
Abstract: Na‐ion hybrid capacitors are an emerging class of inexpensive and sustainable devices that combine the high energy of batteries with the high power of capacitors. However, their development is strongly impeded by a limited choice of electrode materials that display good electrochemical kinetics and long‐term cyclability. Here, a reduced graphene oxide–Zn0.25 V2 O5 · n H2 O nanobelt composite is introduced as a high power anode for Na‐ion batteries and Na‐ion hybrid capacitors. The composite material possesses fast Na‐ion intercalation kinetics, high electronic conductivity, and small volume change during Na‐ion storage, which lead to outstanding rate capability and cycling stability in half‐cell tests. Pairing it with a hard salt–templated, highly ordered mesoporous carbon as a high‐performance capacitive cathode results in a Na‐ion hybrid capacitor, which delivers a high energy density (88.7 Wh kg −1 at 223 W kg −1 ), a high power density (12552 W kg −1 with 13.2 Wh kg −1 retained), and an impressive cycling performance (31.7 Wh kg −1 (i.e., 87%) retained after 2000 cycles at 1 A g −1 ). This work explores zinc vanadate, a typical example of a layered metal vanadate, as an intercalation anode material with high pseudocapacitance for Na‐ion hybrid capacitors, which may open a promising direction for high‐rate Na‐ion storage. Abstract : A composite of reduced graphene oxide and Zn0.25 V2 O5 · n H2 O nanobelts is reported as a new type of Na + intercalation material with high pseudocapacitance, enabling fast sodium storage. Combination of this material as an anode with a capacitive cathode composed of an ordered mesoporous carbon gives access to a high‐performance Na‐ion hybrid capacitor.